Social and Psychological Characteristic of Convicted Women Serving Non-custodial Sentences - N.E. Kolesnikova; O.E. Makarkina (Психология и право, 2022)
The article substantiates the importance of studying criminal female behavior, its prevention. The procedure of socio-psychological diagnostics was carried out on 59 convicted women serving various sentences without isolation from society. The average age of the convicted women is 33 years, the education level is low. The women are either not employed or work in unskilled jobs. They are mostly unmarried or divorced women raising children. The dominant motive of the crimes committed is self-interest. Examining their psychological characteristics revealed impulsivity, underestimation of objective circum-stances and focus on situational desires, a tendency to aggression, conflict situations and antisocial behavior. Based on the identified indicators of the social and psychological development of the personality of convicted women, a number of socio-psychological measures have been proposed to improve their adaptation to life in society and reduce the overall delinquency index.